PENGARUH PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE TWO STAY TWO STRAY (TS-TS) TERHADAP HASIL BELAJAR MAHASISWA EKONOMI UNIVERSITAS MUHAMMADIYAH METRO - Siti Suprihatin (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2019)
Education is a very important element for creating quality, intelligent, peaceful, open, democratic, and able to compete and can improve the welfare of all Indonesian citizens. The state is said to be progressing in all fields both in the fields of economics, technology, agriculture or the other not apart from the role of education. The purpose of this research is to find out the Effect of Two Stay Two Stray Type of Cooperative Learning Model on Student Education Results of Economic Education at Muhammadiyah Metro University. The usefulness is to know the Effect of Cooperative Learning Model Type Two Stay Two Stray (TS-TS) on Student Learning Outcomes of economic education students ", then it can be used as a writer as insight and knowledge. The hypothesis in this study is "There is a positive influence on the use of the Two Stay Two Stray Type Cooperative Learning Model (TS-TS) on Student Learning Outcomes of economic education students". Test the hypothesis using the Simple Linear Regression formula, namely Y '= a + b X value Y' = 50 + 0.4 X followed by the formula thitung which is thit = b / S_b = 3.40. t table = 1.70 (significant level 5%) and t table = 2.46 (significant level 1%), be 3.40> 1.70 at a significant level of 5% and at a significant level of 1%, namely 3.40> 2, 46. Based on the results of these studies, the hypothesis can be accepted because thit = 3.40 is greater than ttab = 1.70 and 2.46. After analyzing the research data, it can be concluded that the analysis of the calculation of the tcount> t table. can be seen in the list of G, at a significant level of 5% which is 3.40> 1.70 and at a significant level of 1% which is 3.40> 2.46. Thus the hypothesis says that there is a positive influence on the use of the Cooperative Learning Model Type Two Stay Two Stray (TS-TS) can improve the learning outcomes of students of economic education. Keywords: Effect of Two Stay Two Stray Type Cooperative Learning Model (TS-TS), learning outcomes.